Shaping Educator Preparation to Build a Stronger Education Workforce - Tanya Pinkerton; Carlyn Ludlow; Jordan M. O. Causadias; Wendy Peia Oakes; Nicole L. Thompson; Heather Villarruel; Carole G. Basile (Education Sciences)
As faculty in a college of education, we have undertaken a multi-year process to redesign pathways leading to teacher certification. Throughout this process, we have confronted challenges in recruiting and retaining teachers, concluding these issues stem from deeper inequities in the current design of the education workforce. To address this, we have implemented new models of educator preparation designed to foster social justice and ensure educators and students alike can thrive. These models emphasize the roles of educators and how they work together as a team with distributed expertise with embedded growth opportunities, and clear paths for career advancement. These models are designed to create inclusive and supportive environments. Central to this redesign, we created holistic systems of care, mitigated long-standing barriers to entry, specialization, and advancement for educators, and liberated content, resulting in increased access for individuals wanting to become educators. In this article, we share insights from our journey of redesigning educator preparation to meet the needs of preservice teachers equipping them to adapt skillfully to dynamic educational demands. Our work aims to reshape educator preparation through fostering a more inclusive, resilient, and sustainable workforce adept to the needs of ever-shifting educational systems.